Well-posedness of the shooting algorithm for control-affine problems with a scalar state constraint - Aronna, M. Soledad; Bonnans, J. Frédéric; Goh, Bean San (Computational & applied mathematics, 2023)
We deal with a control-affine problem with scalar control subject to bounds, a scalar state constraint and endpoint constraints of equality type. For the numerical solution of this problem, we propose a shooting algorithm and provide a sufficient condition for its local convergence. We exhibit an example that illustrates the theory.